2003
DOI: 10.1111/j.1365-2621.2003.tb08264.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation of Convective Heat Transfer Coefficient in Air Impingement Applications

Abstract: Spatial variation of heat transfer is an important factor in air impingement systems. Temperature data were obtained when a jet at room temperature impinged on a flat object initially at -50 °C to estimate heat transfer under freeze-thaw conditions. Single and double circular jets and slot jets were examined. Temperature data were fit into empirical relationships for predicting heat transfer coefficients and their spatial variation for conditions common in impingement freeze-thaw applications. For processing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 15 publications
(20 reference statements)
2
36
0
Order By: Relevance
“…These are within the range of effective heat transfer coefficients reported by Sarkar and Singh [19] for impingement under freeze-thaw conditions, but much lower than others have reported at higher temperatures. Sarkar and Singh's results did not exhibit secondary maxima, as was found in this study, but they did not make measurements of heat transfer coefficient between r/d of 0 and 2.5 in their study.…”
Section: Heat Transfer Coefficients Under Experimental Conditionssupporting
confidence: 65%
See 1 more Smart Citation
“…These are within the range of effective heat transfer coefficients reported by Sarkar and Singh [19] for impingement under freeze-thaw conditions, but much lower than others have reported at higher temperatures. Sarkar and Singh's results did not exhibit secondary maxima, as was found in this study, but they did not make measurements of heat transfer coefficient between r/d of 0 and 2.5 in their study.…”
Section: Heat Transfer Coefficients Under Experimental Conditionssupporting
confidence: 65%
“…Sarkar and Singh [19] measured spatial variation in heat transfer coefficients from air impingement jets under freezethaw conditions by warming a frozen copper plate using room temperature air. They found that average heat transfer coefficients decreased radially away from stagnation.…”
Section: Introductionmentioning
confidence: 99%
“…A customized air-impingement apparatus (as explained by Sarkar and Singh (2003)) was used in this study. Air blowerÕs capacity was 4.72 · 10 À3 m 3 /s at Nomenclature A coefficient used in the finite difference equations A x surface area of a volume element in x-direction, m 2 A y surface area of a volume element in y-direction, m 2 A z surface area of a volume element in z-direction, m 2 a p thermal diffusivity of the plexi-glass, m 2 /s a p thermal diffusivity of the polyurethane foam, m 2 /s c p (i, j, k) heat capacity of a volume element, J/kg K …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the method of using micro-calorimeters developed by Donaldson, Snedeker, and Margolis (1971) and applied by Sarkar and Singh (2003) was used to determine the spatial variation of heat transfer coefficient on the impinging hot surface. The experimental setup used to determine the h-value change was explained in detail by Sarkar and Singh (2003). Fig.…”
Section: Heat Transfer Coefficientmentioning
confidence: 99%
“…(6) h angle measured from stagnation point,°l viscosity, kg m À1 s À1 q density, kg m À3 Lucas et al (1995Lucas et al ( , 1999, Lucas and Raoult-Wack (1996) systems of liquid or air jets impinging on a surface, are proposed in the literature (Martin, 1977;Jambunathan et al, 1992;Lee et al, 1997Lee et al, , 1999Lee et al, , 2007Li and Garimella, 2001;Chan et al, 2002;Sarkar and Singh, 2003;Olsson et al, 2004;Zahran et al, 2006;Robinson and Schnitzler, 2007). Table 2 shows some of the correlations used for jets impinging on surfaces.…”
Section: Nusselt Number Correlationmentioning
confidence: 98%